HUBUNGAN KUALITAS PELAYANAN KEPERAWATAN TERHADAP KEPUASAN PASIEN DI INSTALASI GAWATDARURAT RUMAH SAKIT X JAKARTA BARAT TAHUN 2020 - Royani; Indri Astuti (STIKes IMC Bintaro, 2022)
Introduction The quality of health services is an important component that must be considered by the hospital as a health service facility for the community. The benchmark for service quality can be seen from the level of patient satisfaction, the more perfect patient satisfaction with health services, the value of hospital service standards will also increase. Objective: This study aims to determine the relationship of the effect of service quality on patient satisfaction at the Emergency Installation of Hospital X West Jakarta. Methods: cross sectional, the sample was carried out in the ER X Hospital West Jakarta Number of respondents 178 The data collection technique used was a questionnaire, the analysis technique was carried out through univariate and bivariate tests. The results of this study indicate that 69.7% of respondents stated that the service quality was good and 39.9% of respondents indicated that they were very satisfied with the services provided. There is a relationship between the effect of service quality on patient satisfaction in the Emergency Installation of Hospital X West Jakarta (p = 0.000). Conclusion: There is a relationship between the quality of nursing services and patient satisfaction in the ER X Hospital, West Jakarta. Suggestion: So that the ER X Hospital West Jakarta is able to maintain or improve the quality of service so that patient satisfaction will be maintained and well served.